Pemberdayaan Masyarakat Digital - Genik Puji Yuhanda; Muhibudin Wijaya Laksana (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Digital community empowerment has become an increasingly important topic in the current era of digitalization. In this scientific article, we conduct a literature review to explain the concept, challenges and benefits of digital community empowerment. We analyzed various related articles, books and reports published in recent years to present a comprehensive picture of how digital societal empowerment can be realized and measured. We also discuss the role of information and communications technology (ICT) in increasing community empowerment, as well as the social, economic and political implications of this phenomenon.